Counting on count data models - Rainer Winkelmann (IZA World of Labor, 2015)
Often, economic policies are directed toward outcomes that are measured as counts. Examples of economic variables that use a basic counting scale are number of children as an indicator of fertility, number of doctor visits as an indicator of health care demand, and number of days absent from work as an indicator of employee shirking. Several econometric methods are available for analyzing such data, including the Poisson and negative binomial models. They can provide useful insights that cannot be obtained from standard linear regression models. Estimation and interpretation are illustrated in two empirical examples.
Keywords: C2; C25; 330; Poisson regression; negative binomial distribution; zero-inflation; hurdle model